Bioavailability properties of intravaginal implants made from chitosan-PEG-PCL in simulated vaginal fluid and vagina of cattle - Yessa, Elma Yuliani; Wientarsih, Ietje; Purwantara, Bambang; Amrozi, Amrozi; Ulum, Mokhamad Fakhrul (ARSHI Veterinary Letters, 2023)
This study aimed to design and evaluate the bioavailability of intravaginal implants made from the biodegradable polymer chitosan-polyethylene glycol (PEG)-polycaprolactone (PCL) in simulated vaginal fluid (SVF) and the cow vagina. Implants were prepared using melt-ing and molding techniques with 26 different formulations. Next, the implants were immersed in 40 mL of SVF at a temperature of 37.8 ℃ and changes in implant morphology were observed every day until day 5. Implants that survived until day five were tested for further availability in the cow's vagina and observed daily for 2 weeks. The immersion test on SVF results showed that implants with a PEG content of 75-85% melt more quickly than implants with a PEG content of 20-72%. Implants containing 1-10% PCL eroded more rapidly in the SVF than those containing 22-80% PCL. Implants containing chitosan can remain stable in the SVF for longer than implants without chitosan. The bioavailability test in the cow's vagina showed that implants 21-23 persisted until the 10th day, while implants 24-26 were expelled from the cow's vagina during the test. Implant 21-23 is a promising formulation for the development of biodegradable intravaginal implants. By adjusting the composition of chitosan (between 14-18 wt%), PEG (maximum 72 wt%), and PCL (minimum 20 wt%), intravaginal implants were able to extend the bioavailability of both simulated vaginal fluid and the vagina of cattle.